Optimasi Protokol LEACH Untuk Meningkatkan Stabilitas Pada Wireless Sensor Network - Ahmad Ridwan; Rian Ferdian; Rahmadi Kurnia (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
Wireless sensor networks (WSNs) are small devices that are run by batteries as minimal energy resources. The cluster method is one of the ways on WSN that is widely applied to the routing protocols to extend the network's lifespan. Low-Energy Adaptive Clustering Hierarchy (LEACH) is a cluster-based protocol proven to increase energy efficiency in sensor networks. However, LEACH also has disadvantages such as a selection of cluster heads that don't consider residual energy at every node. It is the cause of failure in the election process and affects the stability of the network cluster. Period network stability is essential as reliable feedback from a network. Therefore, this study tries to investigate and solve stability problems in the LEACH algorithm. In this paper, the authors propose a new protocol that is Optimization-LEACH (O-LEACH), which is the development of the LEACH protocol. The O-LEACH protocol cluster-head selection process is developed based on the initial energy of each node, and a new beginning energy levels calculated from each node to every round. The test results show that the proposed O-LEACH protocol has a better stability period and network lifetime than the LEACH protocol.